Α4 nicotinic acetylcholine receptor modulated by galantamine on nigrostriatal terminals regulates dopamine receptor-mediated rotational behavior. (March 2016) - Inden, Masatoshi; Takata, Kazuyuki; Yanagisawa, Daijiro; Ashihara, Eishi; Tooyama, Ikuo; Shimohama, Shun; Kitamura, Yoshihisa
Abstract: Galantamine, an acetylcholine esterase (AChE) inhibitor used to treat dementia symptoms, also acts as an allosteric potentiating ligand (APL) at nicotinic acetylcholine receptors (nAChRs). This study was designed to evaluate the allosteric effect of galantamine on nAChR regulation of nigrostrial dopaminergic neuronal function in the hemiparkinsonian rat model established by unilateral nigral 6-hydroxydopamine (6-OHDA) injection. Methamphetamine, a dopamine releaser, induced ipsilateral rotation, whereas dopamine agonists apomorphine (a non-selective dopamine receptor agonist), SKF38393 (a selective dopamine D1 receptor agonist), and quinpirole (a selective dopamine D2 receptor agonist) induced contralateral rotation. When 6-OHDA-injected rats were co-treated with nomifensine, a dopamine transporter inhibitor, a more pronounced and a remarkable effect of nicotine and galantamine was observed. Under these conditions, the combination of nomifensine with nicotine or galantamine induced the ipsilateral rotation similar to the methamphetamine-induced rotational behavior, indicating that nicotine and galantamine also induce dopamine release from striatal terminals. Both nicotine- and galantamine-induced rotations were significantly blocked by flupenthixol (an antagonist of both D1 and D2 dopamine receptors) and mecamylamine (an antagonist of nAChRs), suggesting that galantamine modulation of nAChRs on striatal dopaminergic terminals regulates dopamine receptor-mediated movement. Immunohistochemical staining showed that α4 nAChRs were highly expressed on striatal dopaminergic terminals, while no α7 nAChRs were detected. Pretreatment with the α4 nAChR antagonist dihydroxy-β-erythroidine significantly inhibited nicotine- and galantamine-induced rotational behaviors, whereas pretreatment with the α7 nAChR antagonist methyllycaconitine was ineffective. Moreover, the α4 nAChR agonist ABT-418 induced ipsilateral rotation, while the α7 nAChR agonist PNU282987 had no significant effect on rotational behavior. These results suggest that galantamine can enhance striatal dopamine release through allosteric modulation of α4 nAChRs on nigrostriatal dopaminergic terminals. Highlights: Galantamine plus nomifensine induced the ipsilateral rotation in the 6-OHDA-injected rats. α4 nAChR highly expressed in dopaminergic terminals of the striatum. Dihydroxy-β-erythroidine significantly inhibited galantamine-induced rotations. ABT-418 induced the ipsilateral rotational behavior. Galantamine possesses the property of the dopamine release through α4 nAChR.